PENINGKATAN PENGETAHUAN PENCEGAHAN DAN PENGOBATAN HIPERTENSI PADA LANSIA DI RW 14 KELURAHAN TANAH TINGGI JAKARTA PUSAT - Sianturi, Sondang Ratnauli; Ayu, Eka; Tarigan, Diana; Wulandari, Eko Ratnauli (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2024)
Hypertension is one of the health problems experienced by many elderly people. Hypertension causes physical disorders, causing the elderly’s health to become unstable. The unstable health of the elderly is indicated by the presence of symptoms such as headaches in the form of physical activity disorders in hypertensive sufferers can also affect functional and psychosocial status, as well as quality of life. The success of treating hypertension cannot be separated from the knowledge and compliance of the elderly in carrying out hypertension treatment and maintaining a healthy lifestyle. This activity was carried out with the aim of increasing the elderly’s understanding of hypertension and carrying out hypertension exercise movements. This community service activity was carried out in Tanah Tinggi sub-district area Jakarta with a total of 25 elderly people. This activity is divided into 3 sessions, namely hypertension education, making cucumber juice and a hypertension exercise demonstration. The results of this community service show that the elderly have a good understanding of hypertension and good behavior in carrying out hypertension treatment. And the elderly will adopt a healthy lifestyle and perform hypertension exercises regularly both in the community and home. This activity is in collaboration with Posyandu, Posbindu and Puskesmas, so that this activity can run sustainably and can become a joint program.